OPTIMIZATION OF THE SUPPLY CHAIN AT THE ENTERPRISE IN THE CONDITIONS OF CRISIS - Polyanska , A.S.; Martynets , V.B.; Kaban , O.V. (The actual problems of regional economy development, 2022)
The necessity of logistics supply chains research during the war in Ukraine, which caused the crisis in the economic, humanitarian, technical, information environment of enterprises, is substantiated. It is noted that the war in Ukraine added risks to international supply chains, part of which domestic enterprises are. Destroyed or partially damaged by the effects of hostilities, supply chains face many challenges that, if left unchecked, will hamper economic recovery and long-term growth. Features of functioning and management of logistics chains in the conditions of environment change and influence of negative tendencies, in particular decrease in volumes of export and import, change of structure on directions of logistic flows, stop of activity and relocation of the enterprises, increase of risks and threats of goods delivery are considered. The conditions of logistics chains functioning of domestic enterprises in the conditions of war are characterized. Foreign experience of logistics chain optimization is generalized, in particular by identifying and classifying potential and existing risks for them, taking into account the experience gained during the pandemic. It is substantiated that such experience can be partially used to restore and increase the stability of domestic logistics chains in the current conditions of war and post-war recovery. The matrix of risks classification of logistics supply chain management for domestic industrial enterprises is used and adapted. Possible risk management strategies according to the level of complexity of their prediction and impact on them are considered. Criteria for optimizing the management of logistics supply chains based on the selection of the following items are described: identification and maintenance of logistics capacity; ensuring sustainability in the future; creating transparency; assessment of the realism of end-user demand; assessment of the realism of end-user demand. The problem of optimization of logistics supply chain management in the conditions of crisis phenomena is considered. Key indicators of efficiency of functioning of logistics chains on the basis of consideration of both general, and logistical indicators and directions of their optimization on the basis of consideration of optimization criteria considered in article and substantiation key indicators of estimation of such optimization are offered.